اتجاهات السياحة الإلكترونية في الجزائر : افاق وتحديات - صاولي مراد (جامعة الوادي University of Eloued, 2024)
تعتبر السياحة الالكترونية أحدث صور القطاع السياحي لما لها من أهمية على الأداء السياحي والتي تسمح يفتح أسواق الكرتونية عالمية تساهم في تطوير هذا القطاع ،لذالك هدفت هذه الدراسة إلى إبراز مختلف مشاريع إنشاء تطبيقات رقمية مستقبلا للنهوض بالقطاع السياحي الالكتروني في الجزائر معتمدين في ذالك على المنهج الوصفي التحليلي من خلال استعراض الجانب النظري الخاص بالسياحية الإلكترونية ومقوماتها وخصائصها وتشخيص المقومات السياحية الإلكترونية في الجزائر، ومن هنا المنطلق فان ضرورة تطوير القطاع السياحي وتنميته في الجزائر مرتبط بتطوير تكنولوجيا المعلومات و الاتصال التي أصبحت ضرورة حتمية تفرضها طبيعة و جودة و نوعية الخدمات السياحية في تحفيز القطاع السياحي من التقليدي إلى الإلكتروني من أجل الوصول إلى تسهيلات أكثر فعالية للمستهلكين السياحيين، توصلت الدراسة التسويق السياحي الإلكتروني في الجزائر لا يخضع للمعايير التي تخدم التنمية السياحية الداخلية بشكل يتماشى مع التطورات العالمية و رغم الجهود المبذولة إلا أنها تعتبر غير كافية من أجل التطبيق الفعال للسياحة الإلكترونية. The E-tourism is considered the latest form of the tourism sector because of its importance on tourism performance, which allows the opening of global cartoon markets that contribute to the development of this sector. Therefore, this study aimed to highlight various projects for creating digital applications in the future to advance the electronic tourism sector in Algeria, relying in this on the descriptive approach. Analytical by reviewing the theoretical aspect of e-tourism, its components and characteristics, and diagnosing the components of e-tourism in Algeria. From here, the necessity of developing and growing the tourism sector in Algeria is linked to the development of information and communication technology, which has become an inevitable necessity imposed by the nature, quality, and type of tourism services in stimulating the sector. Tourism from traditional to electronic In order to reach more effective facilities for tourist consumers, the study found that electronic tourism marketing in Algeria is not subject to standards that serve internal tourism development in a manner consistent with global developments. Despite the efforts made, they are considered insufficient for the effective application of electronic tourism.
E-tourism trends in Algeria: Prospects and challenges
Keywords: السياحة الالكترونية; الاستثمار السياحي; البرامج الالكترونية